Right Livelihood: A Vital Factor of Moral Purity for Lay Buddhist Disciples - Venerable Kesara (The Journal of International Buddhist Studies College, 2023)
Right livelihood is one of the three factors of moral practice in the moral group of the Noble Eightfold Path, the foundation for other higher practices, namely the practice for concentration and insight wisdom. However, the concept and practice of the right livelihood for moral purity seem to be one of the least discussed topics in Buddhist literature. This article attempts to study right of lay disciples with special reference to Vaṇijjāsutta, Ādiyasutta, Dīghajānusutta of Aṅguttara Nikāya, and Siṅgālovādasutta of Dīgha Nikāya. This paper also applies a qualitative research approach based mainly on documentary analysis. The results show that right livelihood in Buddhist teaching involves both abstinence from the wrong livelihood and taking the right livelihood with the right view and right effort. Buddhist instructions on the right livelihood can enhance a lay disciple both materially and spiritually.